Початок вивчення палеоекономiки в українськiй археологiї (до 100-рiччя вiд дня народження Б. А. Шрамка) - Гаврилюк, Н.О. (Археологія, 2021)
На прикладі наукової біографії видатного українського
вченого, доктора історичних наук, Бориса Андрійовича
Шрамка розглядається зародження палеоекономічного
напрямку у сучасній археологічній науці. Висвітлюються
основні проблеми, що були розглянуті і вирішені дослідником. Показані переваги комплексного археологічного дослідження поселенських структур та нові методи
природничих наук, вперше застосовані Б. А. Шрамком.
Відстоюються пріоритети української археології у дослідженні палеоекономіки давніх суспільств. Для изучения экономических систем древности пригодны почти все модели палеоэкономического исследования,
которые использовались представителями мировой экономической науки. Весьма продуктивными представляются междисциплинарные исследования, в которых сочетаются приемы и методы исследований экономики и археологии. Это направление в англоязычной литературе фиксируется лишь с у 1990-х гг. В украинской археологии
это направление зародилось гораздо раньше. На примере научной биографии Бориса Андреевича Шрамко, доктора исторических наук, создателя харьковской археологической школы, которому в январе 2021 г. исполнилось
бы 100 лет, прослеживается формирование палеоэкономического направления. Показаны основные проблемы,
которые были поставлены и решены исследователем. Отмечено, что вся деятельность ученого имели «адресный»
характер, т. е. перед началом раскопок комплекса археологических памятников округи Бельского городища —
крупнейшей в Восточное Европе поселенческой структуры, Б. А. Шрамко ставил перед собой задачу изучения
экономической системы региона. Показаны достижения ученого в изучении земледелия, скотоводства, ремесел,
домашних промыслов, строительства. Для изучения этих отраслей хозяйства широко использовались методы
естественных наук, т. е. исследования Б. А. Шрамка, начиная с 1960-х гг. имели междисциплинарный характер.
Делается вывод о том, что Б. А. Шрамко первый в Украине провел системное исследование палеоекономики по
методике экономических исследований. Более того, можно говорить, что Б. А. Шрамко доказал Almost all models of the palaeoeconomical researches used by representatives of the world economic science are suitable
for studying the economic systems of antiquity. Interdisciplinary research, which combines the techniques and methods of research in economics and archaeology, seems to be very productive. This trend in the English language literature has
been recorded only since 1990-ies. In Ukrainian archaeology it originated much earlier. On the example of the scientific
biography of Borys Andriiovych Shramko, Doctor of Historical Sciences, the founder of the Kharkiv Archaeological school,
who would have turned 100 in January 2021, the formation of the palaeoeconomic direction can be traced. The main
problems that were posed and solved by the researcher are shown. It is noted that all the activities of the scientist were
«targeted» in nature, i.e. before the start of excavations of the complex of the archaeological monuments in the vicinity of
the Bilsk hill-fort, the largest settlement structure in Eastern Europe, B. A. Shramko set himself the task of studying the
economic system of the region. The achievements of the scientist in the study of agriculture, cattle breeding, crafts, domestic
crafts, construction are shown. To study these branches of the economy, the methods of natural sciences were widely used,
i.e. research by B. A. Shramko, since 1960-ies have had an interdisciplinary character.
It is concluded that B. A. Shramko was the first in Ukraine who conducted a study of the palaeoeconomics using the
method of economic research. Moreover, it can be noted that B. A. Shramko proved the participation of the region he
studied in the world-system structures that developed in the early Iron Age.